Outcomes of cochlear implantation in 75 patients with auditory neuropathy - Wu, Jie; Chen, Jiyue; Ding, Zhiwei; Fan, Jialin; Wang, Qiuquan; Dai, Pu; Han, Dongyi (Frontiers in Neuroscience, 2023)
Cochlear implantation (CI) outcomes in patients with auditory neuropathy (AN) are variable, which hampers patients' decisions on CI. The objective of this study is to assess the outcomes of CI in individuals diagnosed with AN and to examine the various factors that may influence the effectiveness of this intervention. A total of 75 patients diagnosed with AN were included in the study. The hearing threshold, the score of categories of auditory performance (CAP), speech intelligibility rating (SIR), and speech audiometry were tested. Genetic testing was conducted by medical exome sequencing in 46 patients. After CI, the average aided hearing threshold for patients with prelingual and post-lingual onset was 38.25±6.63 dB and 32.58±9.26 dB, respectively; CAP score improved to 5.52±1.64 (P＜0.001) and 6.00±0.96 (P＜0.001), respectively; SIR score increased to 3.57±1.22 (P＜0.001) and 4.15±0.95 (P＜0.001), respectively. Maximum speech recognition ranged from 58% to 93% for prelingual onset patients and 43% to 98% for those with post-lingual onset. Speech outcomes of CI in cases with cochlear nerve (CN) deficiency were significantly poorer (P=0.008). Molecular etiologies, including TWIST1, ACTG1, m.A7445G, and a copy-number variant (CNV) carrying ACTB, were related to AN here. Conclusion: CI is a viable therapy option for patients with AN; CN deficiency might impact outcomes of CI.